Robust Annotation Positioning in Digital Documents - Brush, A.J.; Bargeron, David; Gupta, Anoop; Cadiz, JJ (2000)
Increasingly, documents exist primarily in digital form. System designers have recently focused on making it easier to read digital documents, with annotation as an important new feature. But supporting annotation well is difficult because digital documents are frequently modified, making it challenging to correctly reposition annotations in modified versions. Few systems have addressed this issue, and even fewer have approached the problem from the users’ point of view. This paper reports the results of two studies examining user expectations for “robust” annotation positioning in modified documents. We explore how users react to lost annotations, the relationship between types of document modifications and user expectations, and whether users pay attention to text surrounding their annotations. Our results could contribute substantially to effective digital document annotation systems.